ANALISIS KETERSEDIAAN OBAT DENGAN FORMULARIUM NASIONAL DI PUSKESMAS Y - Neng Widia Ningsih; Tisa Amalia; Aulia Asmawati (INKOFAR, 2025)
Adequate drug availability is a crucial component of healthcare services at Community Health Centers. Drug shortages can disrupt services and reduce patient trust, while overstocking risks expiration and financial loss. The National Formulary (Fornas) serves as a reference for selected drugs to ensure treatment quality. However, its implementation in health facilities still faces challenges. This research aimed to analyze the conformity of drug availability with the National Formulary and the percentage of drug availability level at Y Community Health Center in 2024. The study applied a descriptive method with a retrospective approach. The population included all drugs available from January to December 2024, with a total of 94 types, using total sampling technique. Data were collected from drug stock cards and monthly drug usage reports (LPLPO). Data analysis was performed by comparing the drug list with the National Formulary and calculating drug availability levels based on stock coverage time. The results showed that the conformity rate of drug availability with the National Formulary was 98.94%. Meanwhile, the percentage of drug availability level was categorized as 36.56% insufficient, 24.73% safe, and 38.71% excessive. It is concluded that drug availability at Y Community Health Center has not met the standard indicator of 100% conformity with the National Formulary and 100% safe availability level. This condition indicates inefficiency in drug management planning, which can disrupt rational drug use. Improvements in drug planning and monitoring are recommended.